Enhanced voltammetric anion sensing at halogen and hydrogen bonding ferrocenyl SAMs. Issue 7 (4th January 2021) - Hein, Robert; Li, Xiaoxiong; Beer, Paul D.; Davis, Jason J.
Abstract : Surface enhancement effects in the sensing of anions at redox-active molecular films are investigated in detail and rationalised based on a consideration of the dielectric binding microenvironment. Abstract : Halogen bonding mediated electrochemical anion sensing has very recently been established as a potent platform for the selective and sensitive detection of anions, although the principles that govern binding and subsequent signal transduction remain poorly understood. Herein we address this challenge by providing a comprehensive study of novel redox-active halogen bonding (XB) and hydrogen bonding (HB) ferrocene-isophthalamide-(iodo)triazole receptors in solution and at self-assembled monolayers (SAMs). Under diffusive conditions the sensory performance of the XB sensor was significantly superior. In molecular films the XB and HB binding motifs both display a notably enhanced, but similar, response to specific anions. Importantly, the enhanced response of these films is rationalised by a consideration of the (interfacial) dielectric microenvironment. These effects, and the resolved relationship between anion binding and signal transduction, underpin an improved fundamental understanding of anion sensing at redox-active interfaces which will benefit not just the development of more potent, real-life relevant, sensors but also new tools to study host–guest interactions at interfaces.